Composite products and their manufacturing

By preparing composite products containing glass, adhesives and fillers, the problem of waste of waste glass and other waste resources is solved, and the preparation of high-quality composite products is achieved, with good mechanical properties and low moisture absorption.

JP7655857B2Active Publication Date: 2025-04-02NEWSOUTH INNOVATIONS PTY LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021558856
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-04-03
Filing Date
2020-04-03
Publication Date
2025-04-02
Estimated Expiration
2040-04-03

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize discarded glass and other common wastes, converting them into valuable products, resulting in waste of resources.

Method used

By preparing composite products containing glass, adhesives and fillers such as textiles, paper cups and coffee grounds, these materials are combined into useful products using hot pressing or injection molding processes.

Benefits of technology

A method of converting waste glass and other waste into high-quality composite products is realized, reducing resource waste, and the product has good mechanical properties and low moisture absorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655857000014
    Figure 0007655857000014
  • Figure 0007655857000015
    Figure 0007655857000015
  • Figure 0007655857000016
    Figure 0007655857000016
Patent Text Reader

Abstract

FIELD OF THE INVENTION The present invention relates generally to composite products, and more particularly to glass-based composite products and their manufacture.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THEINVENTION This invention relates generally to composite products, and more particularly to glass-based composite products and their manufacture. [Background technology]

[0002]

[0002] Throughout this specification, any discussion of prior art is not intended as an admission that such prior art is widely known or forms part of the common general knowledge in the art.

[0003]

[0003] The amount of waste generated by the world's population continues to grow at an alarming rate. In 2014 / 2015, Australians alone generated 64 million tonnes of waste. Waste glass is also on the rise in Australia, with around 150,000 tonnes going to landfill per year. Summary of the Invention [Problem to be solved by the invention]

[0004]

[0004] The present inventors have developed a method for making glass-based composite products that allows not only waste glass, but also other common waste materials to be converted into useful products. [Means for solving the problem]

[0005] [Summary of the Invention]

[0005] In a first aspect of the present invention, there is provided a composite product comprising glass, a binder, and at least one filler selected from textile, paper cups, and coffee grounds.

[0006] The binder can be present in an amount of from about 5% to about 45% by weight, or from about 15% to about 40% by weight.

[0007] The glass can be present in an amount of about 50% to about 90% by weight, or about 50% to about 75% by weight.

[0008]

[0008] The at least one filler can be present in an amount of about 1% to about 30% by weight, or about 2.5% to about 15% by weight.

[0009] The particle size of the glass may be less than about 5 mm.

[0010]

[0010] The particle size of the glass may be from about 1 μm to about 5 mm.

[0011] The particle size of the glass may be less than about 300 μm, or less than about 200 μm, or less than about 150 μm.

[0012] The particle size of the glass may be between about 1 μm and about 100 μm, or between about 5 μm and about 70 μm.

[0013]

[0013] The glass may be in powder form.

[0014]

[0014] The glass may be waste glass.

[0015] The binder may be a polymer.

[0016] The polymer may be a thermosetting polymer.

[0017]

[0017] The thermosetting polymer may be an epoxy resin, a polyester resin, or a vinyl ester resin. In one embodiment, the thermosetting polymer is a polyester resin.

[0018]

[0018] The paper cup may be a disposable paper cup.

[0019]

[0019] The disposable paper cup may be a disposable paper cup for coffee.

[0020]

[0020] The textile product may be clothing, linen, bedding, a blanket, or a curtain.

[0021]

[0021] The textile product may be a synthetic textile product.

[0022]

[0022] The at least one filler may be coffee grounds.

[0023]

[0023] At least one filler may be a fibrous product.

[0024]

[0024] At least one filler may be a paper cup.

[0025] The complex may further comprise a coupling agent.

[0026] The coupling agent may be a silane.

[0027] The composite may further comprise a pigment.

[0028]

[0028] The composite may be in the form of a panel or a tile.

[0029]

[0029] The composite may contain greater than about 50% by weight waste material, or greater than about 60% or greater than about 70%.

[0030]

[0030] The composite may further include a coating.

[0031]

[0031] The coating may be an epoxy coating or a polyurethane coating.

[0032] The composite may be made by hot pressing or casting.

[0033] In a second aspect of the present invention, there is provided a method for making a composite product comprising: (i) forming a mixture comprising glass, a binder, and at least one filler selected from textiles, paper cups, and coffee grounds; (ii) applying heat and pressure to the mixture to form a composite product.

[0034] The binder may be present in the mixture in an amount of from about 5% to about 45%, or from about 15% to about 40% by weight.

[0035]

[0035] The glass can be present in the mixture in an amount of about 50% to about 90% by weight, or in an amount of about 50% to about 75% by weight.

[0036]

[0036] The at least one filler can be present in the mixture in an amount of from about 1% to about 30% by weight, or from about 2.5% to about 15% by weight.

[0037]

[0037] The glass, binder and at least one filler may be as defined in the first embodiment.

[0038]

[0038] The glass may be dried prior to forming the mixture.

[0039]

[0039] The glass may be dried at least at about 400°C prior to forming the mixture.

[0040] The mixture may further comprise a catalyst.

[0041] The catalyst may be present in the mixture in an amount of from about 0.1% to about 10% by weight, or from about 0.5% to about 5% by weight, based on the weight of the binder.

[0042] The mixture may further include a pigment.

[0043] The mixture may further comprise an inhibitor.

[0044] The inhibitor may be present in the mixture in an amount of about 0.01% to about 2% by weight, or about 0.05% to about 0.5% by weight, based on the weight of the binder.

[0045] The mixture may further comprise a coupling agent.

[0046] The glass may be pre-treated with a coupling agent.

[0047] The coupling agent may be a silane.

[0048]

[0048] The paper cups and textile products may be in the form of aggregates or fibers in the mixture.

[0049]

[0049] Prior to forming the mixture, the coffee grounds may be dried.

[0050]

[0050] Prior to forming the mixture, the coffee grounds may be sieved through a 1 mm mesh sieve.

[0051] Step (i) may be carried out as follows: - The glass and the binder are combined and mixed, and then at least one filler is added to obtain a mixture.

[0052] Step (i) may be carried out as follows: forming a first mixture comprising a glass and a binder and mixing the first mixture; - combining a catalyst with the first mixture to form a second mixture and mixing the second mixture; - combining at least one filler with the second mixture and mixing to obtain a mixture;

[0053] The glass may be pre-treated with a coupling agent.

[0054] The coupling agent may be a silane.

[0055] The first mixture may further include an inhibitor.

[0056] The first mixture may further include a pigment.

[0057]

[0057] The first mixture and the second mixture may be mixed for about 5 minutes to about 1 hour, or about 15 minutes to about 45 minutes, or about 30 minutes.

[0058] The at least one filler and the second mixture may be mixed for about 5 minutes to about 1 hour, or about 15 minutes to about 45 minutes, or about 30 minutes.

[0059]

[0059] Step (ii) may be carried out by filling the mixture into a die and pressing it in a hydraulic press.

[0060] In a third aspect, the present invention provides a method for making a composite product comprising: (i) forming a mixture comprising glass, a binder, and at least one filler selected from textiles, paper cups, and coffee grounds; (ii) filling the mixture into a mould; (iii) drawing a vacuum on the mixture to obtain a composite; The present invention provides a method comprising:

[0061] The method includes: (iv) separating the complex from the mold.

[0062]

[0062] The vacuum may be at a pressure between about 10 mmHg and about 50 mmHg, or about 30 mmHg.

[0063]

[0063] The evacuation may be carried out for about 12 to 24 hours.

[0064]

[0064] The glass, binder and at least one filler may be as defined in the first embodiment.

[0065]

[0065] The glass, binder, and at least one filler may be present in the mixture in the amounts described above in relation to the second embodiment.

[0066]

[0066] The glass may be dried prior to forming the mixture.

[0067]

[0067] The glass may be dried at a temperature of at least 400°C prior to forming the mixture.

[0068] The mixture may further comprise a catalyst.

[0069] The catalyst can be present in the mixture in an amount of from about 0.1% to about 10% by weight, or from about 0.5% to about 5% by weight, based on the weight of the binder.

[0070]

[0070] The mixture may further include a pigment.

[0071] The mixture may further comprise an inhibitor.

[0072]

[0072] The inhibitor may be present in the mixture in an amount of about 0.01% to about 2% by weight, or in an amount of about 0.05% to about 4% by weight.

[0073] The mixture may further comprise a coupling agent.

[0074] The glass may be pre-treated with a coupling agent.

[0075] The coupling agent may be a silane.

[0076]

[0076] The paper cups and textile products may be in the form of aggregates or fibers in the mixture.

[0077]

[0077] Prior to forming the mixture, the coffee grounds may be dried.

[0078]

[0078] Prior to forming the mixture, the coffee grounds may be sieved through a 1 mm mesh sieve.

[0079] Step (i) may be carried out as follows: forming a first mixture comprising an inhibitor and a binder and mixing the first mixture; - combining the first mixture with a glass and a catalyst to form a second mixture and mixing the second mixture; - combining at least one filler with the second mixture and mixing to obtain a mixture;

[0080]

[0080] The glass may be pre-treated with a coupling agent.

[0081] The coupling agent may be a silane.

[0082]

[0082] The first mixture may be allowed to stand for at least 2 hours after mixing.

[0083] The at least one filler and the second mixture may be mixed for about 30 minutes to about 90 minutes, or about 60 minutes.

[0084] In a fourth aspect, the present invention provides a composite product obtainable by the method of the second or third aspect.

[0085] [Definition]

[0085] Throughout this specification, unless the context requires otherwise, the word "comprise" or variations thereof such as "comprises" or "comprising" will be understood to imply the inclusion of a stated element, integer, or step or group of elements, integers, or steps, but not the exclusion of any other element, integer, or step or group of elements, integers, or steps. Thus, the word "comprising" in the context of this specification means "including primarily, but not necessarily only."

[0086] In the context of this specification, the words "a" and "an" are used herein to refer to one or to more than one (i.e., to at least one) of the grammatical object of the article. By way of example, "an element" means one element or more than one element.

[0087]

[0087] The term "about" is understood to refer to a range of numbers that one of ordinary skill in the art would consider equivalent to the recited value for achieving the same function or result. [Brief description of the drawings]

[0088]

[0088] Embodiments of the present invention will now be described, by way of example only, with reference to the accompanying drawings.

[0089] [Figure 1] 1 is a method for making a composite article according to one embodiment of the present invention. [Diagram 2] 1A-1D are examples of composite products made in accordance with embodiments of the present invention: (a) a composite panel made from waste glass powder and micronized paper cups (from coffee cups); (b) a composite panel made from waste glass powder and coffee grounds; (c) a composite panel made from waste glass powder and paper cup aggregate (from coffee cups); and (d) a composite panel made from waste glass powder and fiber aggregate. [Diagram 3] Bending strength of hot-pressed panels. [Figure 4] Compressive strength of hot-pressed panels. [Diagram 5] is the density of the hot pressed panel. [Figure 6] is the penetration depth of the hot pressed panel. [Figure 7] 1 is a wear profile of a hot pressed panel. [Figure 8] 1. Stain profiles of hot pressed panels: (a) Sample 1, (b) Sample 2, and (c) Sample 3. [Figure 9] Casting method and equipment. [Figure 10] Flexural strength of fiber-containing panels. [Figure 11] Compressive strength of fiber-containing panels. [Figure 12] The density of the fiber-containing panel. [Figure 13] Water absorption rate of fiber-containing panels. [Figure 14] Penetration depth of polyurethane coating (Shore D80). [Figure 15] (A–D) Wear profiles of coated composite panels and different stones; (F) Correlation between wear resistance and toughness. [Figure 16] Stain testing of coated composite panels. [Figure 17] Bending strength of a glass / polyester resin panel containing a coffee cup and coffee grounds. [Figure 18] Compressive strength of a glass / polyester resin panel containing a coffee cup and coffee grounds. [Figure 19] Density of a glass / polyester resin panel containing a coffee cup and coffee grounds. [Figure 20] Water absorption rate of a glass / polyester resin panel containing a coffee cup and coffee grounds. [Figure 21]XRD analysis of powders from (a) glass; (b) crushed polyester / glass / fiber panels (fine powder); (c) recovered cutting residue of polyester / glass / fiber panels. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0090] [Detailed Description]

[0089] The present invention broadly relates to a composite product comprising glass, a binder, and at least one filler selected from textiles, paper cups, and coffee grounds.

[0091]

[0090] In making the composite product, the inventors have found that it is possible to successfully encapsulate the textile, paper cup, and coffee grounds in a binder. The textile also provides the product with a characteristically beautiful appearance. It has also been surprisingly found that the textile-containing product and the paper cup-containing product are self-extinguishing. The product can also be made at low cost, since it is typically composed of at least 50%-80% by weight of waste material. Furthermore, the product is lighter in weight and has a density of about 0.3-0.7 g / cm. 3 , which is lower than generic ceramic tiles or natural marble and granite. This allows for cheaper and easier shipping. It is also observed that the product has greater stability, with minimal shrinkage and warping, compared to products made from glass and binders alone. Furthermore, products containing textiles may have better acoustic properties than generic ceramic tiles, by reducing the transmission of sound vibrations and excessive reverberation.

[0092]

[0091] The binder can be present in an amount of about 5% to about 45% by weight, or in an amount of about 10% to about 50% by weight, or in an amount of about 5% to about 40% by weight, or in an amount of about 5% to about 35% by weight, or in an amount of about 5% to about 30% by weight, or in an amount of about 5% to about 25% by weight, or in an amount of about 10% to about 25% by weight, or in an amount of about 15% to about 20% by weight, or in an amount of about 15% to about 45% by weight, or in an amount of about 15% to about 40% by weight, or in an amount of about 20% to about 35% by weight, or in an amount of about 20% to about 40% by weight.

[0093]

[0092] The glass can be present in an amount of about 40% to about 90% by weight, or in an amount of about 50% to about 90% by weight, or in an amount of about 50% to about 85% by weight, or in an amount of about 55% to about 85% by weight, or in an amount of about 60% to about 80% by weight, or in an amount of about 55% to about 85% by weight, or in an amount of about 55% to about 75% by weight, or in an amount of about 60% to about 75% by weight.

[0094]

[0093] At least one filler can be present in an amount of about 1% to about 30% by weight, or in an amount of about 1% to about 25% by weight, or in an amount of about 5% to about 30% by weight, or in an amount of about 5% to about 25% by weight, or in an amount of about 10% to about 25% by weight, or in an amount of about 2.5% to about 15% by weight, or in an amount of about 5% to about 10% by weight, or in an amount of about 5% to about 15% by weight.

[0095]

[0094] Typically, the binder is a polymer. Suitable polymers include, but are not limited to, acrylonitrile butadiene styrene, polylactic acid, styrene acrylonitrile, polypropylene, polyethylene, high density polyethylene, low density polyethylene, linear low density polyethylene, ultra-high molecular weight polyethylene, polyvinyl chloride, polyethylene terephthalate, nylon, polystyrene, high impact polystyrene, polyoxymethylene (acetal), poly(methyl methacrylate), polyester, or polycarbonate.

[0096] In some embodiments, the polymer is a thermosetting polymer. Thermosetting polymers, thermosetting resins, or thermosetting plastics, also referred to as "thermosets," are polymers that irreversibly harden by curing a soft solid or viscous liquid prepolymer or resin. Curing can be induced by heat or radiation, or accelerated by high pressure or by mixing with a catalyst. Curing results in extensive cross-linking between polymer chains, producing a non-meltable and non-soluble polymer network. Examples of thermosetting polymers include, but are not limited to, polyester resins, polyurethanes, polyureas / polyurethanes, vulcanized rubber, bakelite, duroplast, urea-formaldehyde, melamine resins, diallyl phthalates, epoxy resins, benzoxazines, polyimides, bismaleinides, cyanate esters, furan resins, silicone resins, thiolytes, and vinyl ester resins. In some embodiments, the thermosetting polymer can be, or is derived from, an epoxy resin, a polyester resin, or a vinyl ester resin, hi other embodiments, the thermosetting polymer can be, or is derived from, an unsaturated polyester resin.

[0097]

[0096] Depending on the type of thermosetting polymer, a catalyst may also be used in the preparation of the composite. Catalysts are used to promote crosslinking of the polymer, which leads to hardening, also known as curing. Suitable curing agents / catalysts are known to those skilled in the art and include, for example, radical initiators such as organic peroxides. Non-limiting examples of organic peroxides include benzoyl peroxide, 2-butanone peroxide, methyl ethyl ketone peroxide (MEKP), and t-butyl peroxybenzoate (TPB).

[0098]

[0097] When preparing a composite, the catalyst can be added to the mixture in an amount of about 0.1% to about 10% by weight, or about 0.5% to about 5% by weight, or about 0.5% to about 4% by weight, or about 0.5% to about 3% by weight, based on the weight of the binder contained in the composite.

[0099] In some embodiments, inhibitors are used in the preparation of the composite. Inhibitors are antioxidant molecules that act to trap free radicals, thereby preventing premature spontaneous free radical polymerization from initiating and propagating, and thus preventing the thermosetting polymer from hardening. Thus, inhibitors can be used to control the hardening rate of the polymer. Suitable inhibitors are known to those skilled in the art and include butylated hydroxytoluene (BHT) and monomethyl ether hydroquinone (MEHQ).

[0100]

[0099] When preparing a complex, the inhibitor can be added to the mixture in an amount of about 0.01% by weight to about 2% by weight, or in an amount of about 0.05% by weight to about 1% by weight, or in an amount of about 0.05% by weight to about 0.5% by weight, or in an amount of about 0.1% by weight to about 0.5% by weight, based on the weight of the binder to be contained in the complex.

[0101]

[0100] Glass suitable for use in the composite product can be obtained from any source. Preferably, the glass is waste glass, such as discarded glass containers / bottles, etc. Other sources of waste glass include glass obtained from the construction and automotive industries. In some embodiments, the waste glass is mixed waste glass, i.e., waste glass obtained from multiple sources is mixed together. Preferably, the glass is washed before use. In some embodiments, the glass is provided in the form of a powder or beads. In other embodiments, the glass is provided in the form of an aggregate. Preferably, the waste glass is dried before use. For example, the waste glass can be dried at a temperature of at least about 100°C, or at least about 200°C, or at least about 300°C, or at least about 400°C. Drying can be performed for about 1 hour to about 24 hours depending on the mass of the glass. The drying step can also serve to facilitate the removal of moisture and organic materials and to inactivate organic compounds such as paper and plastic in the composite.

[0102]

[0101] In some embodiments, the particle size of the glass is less than about 5 mm, or less than about 4 mm, or less than about 3 mm, or less than about 2 mm, or less than about 1 mm. In other embodiments, the particle size of the glass is less than about 900 μm, or less than about 800 μm, or less than about 700 μm, or less than about 600 μm, or less than about 500 μm, or less than about 400 μm, or less than about 300 μm, or less than about 200 μm, or less than about 150 μm, or less than about 120 μm, or between about 50 μm and about 150 μm. In one embodiment, the glass is waste glass that passes through a 5 mm sieve.

[0103]

[0102] In other embodiments, the particle size of the glass is between about 1 μm and about 5 mm, or between about 1 μm and about 1 mm, or between about 1 μm and about 500 μm, or between about 1 μm and about 300 μm, or between about 1 μm and about 200 μm, or between about 1 μm and about 100 μm, or between about 1 μm and about 80 μm.

[0104]

[0103] In further embodiments, the particle size of the glass is between 40 μm and about 100 μm, or between about 25 μm and about 250 μm, or between about 50 μm and about 200 μm, or between about 20 μm and about 500 μm, or between about 10 μm and about 500 μm, or between about 10 μm and about 750 μm. In further embodiments, the glass is provided in the form of particles or granules with a size of about 40 μm to about 5 mm. When high mechanical strength is required, it is preferable to use glass powder for the preparation of the composite.

[0105]

[0104] The composite may have poor bonding adhesion due to the interaction between the organic and inorganic materials, which reduces the wettability of each component. The binder comprises a hydrocarbon, which is hydrophobic, while the glass is hydrophilic. Thus, in some embodiments, the composite may further comprise a coupling agent. The coupling agent reacts with the glass surface to modify the surface, which makes it more reactive with the binder. Without wishing to be bound by a particular theory, it is believed that the coupling agent, once attached to the glass surface, improves the contact angle or wettability of the binder on the glass surface, thereby enhancing the bond between the glass and the binder.

[0106] In one embodiment, the coupling agent is a silane. Silane coupling agents typically have the following structure: (RO)3-Si-R'-X, where X is an organic functional group, R' is an alkylene bond, and RO is a hydrolyzable group, such as an alkoxy group. The hydrolyzable group reacts with hydroxyl groups on the glass to provide a modified surface, and the organic functional group then reacts with the binder to form strong covalent bonds that enhance the strength of the composite. In one embodiment, the silane is β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane. In another embodiment, the silane is 3-glycidoxypropyltrimethoxysilane. Other suitable silanes will be known to those skilled in the art. Typically, the glass is pretreated with a coupling agent before reacting with the binder.

[0107]

[0106] In another embodiment, the coupling agent can be a maleic polyolefin-based coupling agent. The maleic polyolefin-based coupling agent can be used to enhance the bonding between glass and polyolefin binders (e.g., polyethylene (PE), polypropylene (PP), high density polyethylene (HDPE), polyvinyl chloride (PVC), etc.). The coupling agent contains two main components, namely, one of the polyolefin-type polymers (listed above) and maleic anhydride functional groups grafted onto the polymer backbone. When the grafted polyolefin coupling agent is melted with a polymer having a similar composition (e.g., maleic anhydride grafted PE and PE, or MA-PP coupling agent and PP) and then cooled, the polymeric groups in the coupling agent crystallize and bond to the polymer substrate, while the maleic anhydride groups in the coupling agent react with the hydroxyl groups of the glass to form strong covalent ester bonds.

[0108]

[0107] The coupling agent can be present in an amount of from about 0.5% to about 3% by weight, or from about 0.5% to about 2% by weight, based on the weight of the glass included in the composite.

[0109]

[0108] In some embodiments, the paper cup is a disposable paper cup, such as, for example, a disposable paper cup for coffee. Disposable paper cups for other beverages, such as soft drinks, water, slushies, etc., can also be used. It is estimated that 1 billion paper coffee cups are discarded each year in Australia. Many of these cups end up in landfill. Preferably, the moisture content of the paper cup is less than about 10%, less than 9%, less than 8%, less than 7%, less than 6%, less than 5%, less than 4%, less than 3%, less than 2%, or less than 1%.

[0110]

[0109] Examples of textile products that may be included in the composite include, but are not limited to, clothing, linen products, bedding, blankets, and curtains. It is estimated that each Australian disposes of about 23 kg of clothing per year, of which about 85% ends up in landfill. In some embodiments, the textile product may be a synthetic textile product. Preferably, the moisture content of the textile product may be less than about 10%, less than 9%, less than 8%, less than 7%, less than 6%, less than 5%, less than 4%, less than 3%, less than 2%, or less than 1%.

[0111]

[0110] In Sydney alone, cafes and coffee shops generate approximately 3000 tonnes of coffee grounds. Most of these grounds are either taken to landfill or flushed down the sink. Advantageously, the coffee grounds can be incorporated into the composite without further processing other than drying. However, in some embodiments, the coffee grounds can be sieved through a 1 mm mesh sieve to provide a more uniform particle size. Preferably, the moisture content of the coffee grounds is less than about 10%, less than 9%, less than 8%, less than 7%, less than 6%, less than 5%, less than 4%, less than 3%, less than 2%, or less than 1%.

[0112]

[0111] The composite may also include one or more pigments. The pigments may be selected depending on the desired color of the composite. In one embodiment, natural pigments such as TiO2, Fe2O3, carbon, or fly ash may be added in powder form. In other embodiments, synthetic powder or liquid pigments may be incorporated into the composite product to achieve a wide range of color palettes.

[0113]

[0112] The composite may further include a coating. The coating improves the abrasion resistance and water resistance of the composite, as well as providing a smooth surface finish. In some embodiments, the coating may be an epoxy coating, a polyaspartic acid, or a polyurethane coating. The Shore D hardness value of the coating may be between about 70 and 90, or about 80.

[0114]

[0113] By utilizing waste streams to create composite products, waste materials that would otherwise end up in landfills are used to create valuable new products. In one embodiment, the composite product can be made in panel form as an internal horizontal surface, such as a tabletop or benchtop. When made from waste materials, the panel is less expensive than, for example, stone or engineered stone panels, while still looking and feeling very similar. In another embodiment, the composite product can be used as exterior wall cladding or splashback for buildings.

[0115]

[0114] The composite may contain greater than about 50%, or greater than about 60%, or greater than about 70%, or greater than about 80% by weight of waste material.

[0116]

[0115] In some embodiments, the conjugate comprises: -about 50% to about 90% by weight of glass; - from about 1% to about 20% by weight of at least one filler; -Binder: about 10% to about 45%; Includes.

[0117] In another embodiment, the conjugate is: -about 50% to about 80% by weight of glass; - from about 2% to about 15% by weight of at least one filler; -Binder: about 15% to about 40%; Includes.

[0118]

[0117] In a further embodiment, the conjugate comprises: - about 60% to about 70% by weight of glass; - from about 5% to about 10% by weight of at least one filler; -Binder: about 20% to about 35%; Includes.

[0119] In a further embodiment, the conjugate comprises: about 55% to about 75% by weight of glass; - from about 2.5% to about 15% by weight of at least one filler; -Binder: about 15% to about 40%; Includes.

[0120] In a further embodiment, the conjugate comprises: about 65% to about 75% by weight of glass; - from about 2.5% to about 7.5% by weight of at least one filler; -Binder: about 20% to about 30%; Includes.

[0121] In a further embodiment, the conjugate comprises: about 55% to about 65% by weight of glass; - from about 2% by weight to about 10% by weight of at least one filler; -Binder: approx. 30% to approx. 40%; Includes.

[0122] In the above-described embodiments, the glass may have any particle size as defined herein.

[0123]

[0121] The composite according to the present invention can be made by hot pressing. In one embodiment, the composite can be made by hot pressing as shown in Figure 1. In this embodiment, waste glass is crushed, for example by a hammer or jaw crusher, and dried in a dryer to remove moisture. The waste glass cullet is then crushed into powder. A suitable resin and catalyst / hardener are then combined and subsequently mixed with the glass powder to form a thick paste (referred to as "first mix"). Filler is then added to this paste and further mixed (referred to as "second mix") to obtain the final blend. The final blend is then formed into the desired shape in a mold, sealed with a lid, and placed in a hydraulic press. After compression, the product is cooled and then removed from the mold.

[0124]

[0122] Premixing the glass powder and resin before adding the filler prevents excessive resin from being absorbed by the highly absorbent filler. This two-stage mixing minimizes the amount of resin used and also prevents resin from leaking out of the filler during compression. Typically, the resin and glass powder are mixed for about 5 minutes, after which the filler is added and then mixed for another 5 minutes.

[0125]

[0123] In another embodiment, the composite is made by forming a first mixture including glass and binder, mixing the first mixture; forming a second mixture by combining the first mixture with a catalyst, mixing the second mixture; combining at least one filler with the second mixture and further mixing. Preferably, mixing is performed using a Sigma (or z-arm) mixer. The resulting mixture can then be hot pressed as follows: The press and carbon steel mold are preheated to a temperature of about 100 to about 200°C, or about 135 to about 140°C. A release agent (e.g., calcium stearate, etc.) is then applied to the mold to facilitate removal of the composite after pressing. Alternatively, a release agent can be included in the mixture. The mixture is then hand-laid into the heated mold and the surface is smoothed. A steel square lid is placed on top, and the closed mold is then placed in a hydraulic hot press and compressed at a pressure of about 150 bar for about 15 minutes. The composite is then removed from the mold. Optionally, the mold can be cooled to room temperature for at least 1.5 hours before demolding. The produced panel can then be stored under low load for about 24 hours to ensure flatness. In this embodiment, mixing can be carried out for about 5 minutes to about 1 hour, or about 15 minutes to about 45 minutes, or about 30 minutes. Typically, hot pressing is carried out at a temperature of about 80°C to about 250°C, or about 80°C to about 200°C, and under a pressure of about 100 bar to about 550 bar.

[0126]

[0124] In an alternative embodiment, the composite can be made by casting. Casting involves forming a mixture including glass, binder and at least one filler, filling the mixture into a mould base, smoothing the surface of the mixture, and then placing a lid. The mixture is then vacuumed. Typically, vacuuming is performed at a pressure of about 30 mmHg for about 12 to 24 hours. The hardened composite is then removed from the mould.

[0127] In another embodiment, the composite is made by forming a first mixture including an inhibitor and a binder; mixing the first mixture; forming a second mixture by combining a glass and a catalyst with the first mixture, mixing the second mixture, combining at least one filler with the second mixture, and further mixing. Preferably, the first mixture is allowed to stand for at least about 2 hours after mixing. This allows the resin and inhibitor to react before the catalyst is introduced. The resulting mixture is mixed for about 5 minutes using a hand mixer. The mixture is then poured into a mold and the surface is smoothed. A mould top is then placed on top of the mixture. The entire casting slab is then covered with a vacuum bag and a breather is evenly spread over the entire top mold. The breather facilitates the drawing of air from the bag into the vacuum pump. A vacuum pressure of between about 1 mmHg and about 200 mmHg, or between about 10 mmHg and about 50 mmHg, or about 30 mmHg is applied to the form for at least 12 to 24 hours. Preferably, the injection, surface smoothing, and application of vacuum pressure are completed within about 50 to 90 minutes, or more preferably within about 60 minutes.

[0128]

[0126] The preparation of the composite by hot pressing and casting is described in detail below. EXAMPLES

[0129]

[0127] A composite according to an embodiment of the present invention was prepared as follows.

[0130] Example 1 Material preparation Waste glass

[0128] The mixed waste glass was crushed into aggregates of 10-40 mm size using a hammer or jaw crusher, and the moisture was removed by drying in a 100°C oven for 3 hours. The waste glass cullet was then ground into a fine powder using a ring mill. When laminated glass was introduced into this process, the polyvinyl butyral layer remained in the form of spheres of 10 mm or more or 20 mm or more in diameter, and was easily removed by sieving through a 108 μm metal sieve.

[0131] Paper cups and textile products

[0129] The paper cups and textile products are mechanically cut using a shredder to form aggregates of 10-30 mm. Depending on the design desired for the final product, the paper cups and textile products can be further ground into fibers of 0.5 mm size by a knife mill. The latter will make the final product look more homogenous. The paper cups and textile products are then dried in a dryer to reach a moisture level of 5% or at least dried at 100°C for 3 hours.

[0132] Coffee grounds

[0130] The coffee grounds were sieved through a 1 mm mesh sieve and dried in an oven to reach a moisture level of 5% or dried at least at 100°C for 3 hours.

[0133] binder

[0131] The binder used in this example is Epoxycast Clear Casting Resin available from Barnes Products Pty Ltd (http: / / www.barnes.com.au / epoxy-resin / epoxycast-clear-Casting-resin-1240?Searchquery=epoxycast&results=1). R180 epoxy resin from Allnex can also be used. Epoxy casting resins are characterized by being of medium viscosity, non-toxic, and excellent chemical and abrasion resistance. The resin was mixed with the hardener in a 2:1 volume ratio. The resin gelled within 20-40 minutes when reacted isothermally at room temperature.

[0134] method Method 1 - Preparation of composite panels from waste glass and coffee grounds

[0132] A panel of dimensions 240mm x 240mm x 15mm was prepared as follows.

[0135] 960 g of mixed waste glass was mixed with 320 g of resin for approximately 5 minutes. 320 g of coffee grounds were then added, followed by mixing for an additional 5 minutes. The resulting mixture was hand laid up into a 240 mm x 240 mm carbon steel mould lined with a non-stick Teflon sheet. The surface of the mixture was then smoothed and sealed with a square steel lid. The sealed mould was placed in a hydraulic hot press preheated to 80°C and compressed at 500 bar pressure for 60 minutes. The mould was then cooled at room temperature for at least 30 minutes before the sample was removed from the steel mould. This panel is shown in Figure 2(b).

[0136] Method 2 - Making composite panels from waste glass and textile products

[0134] A panel of dimensions 240mm x 240mm x 15mm was prepared as follows.

[0137] 780 g of mixed waste glass was mixed with 260 g of resin for approximately 5 minutes. Then, 260 g of textile product (in the form of a shredded polyester / cotton blend) was added, followed by mixing for another 5 minutes. The resulting mixture was hand laid up into a 240 mm x 240 mm carbon steel mould lined with a non-stick Teflon sheet. The surface of the mixture was then smoothed and sealed with a square steel lid. The sealed mould was placed in a hydraulic hot press preheated to 80°C and compressed at a pressure of 500 bar for 60 minutes. The mould was then cooled at room temperature for at least 30 minutes before the sample was removed from the steel mould. This panel is shown in Figure 2(d).

[0138] Method 3 - Fabrication of composite panels from waste glass and discarded coffee cups

[0136] A panel of dimensions 240mm x 240mm x 15mm was prepared as follows.

[0139] 780 g of mixed waste glass was mixed with 260 g of resin for approximately 5 minutes. 260 g of discarded coffee cups (as 0.5 mm fibres) were then added, followed by mixing for an additional 5 minutes. The resulting mixture was hand laid up into a 240 mm x 240 mm carbon steel mould lined with non-stick Teflon sheet. The surface of the mixture was then smoothed and sealed with a square steel lid. The sealed mould was placed in a hydraulic hot press preheated to 80°C and pressed at 500 bar pressure for 60 minutes. The mould was then cooled at room temperature for at least 30 minutes before the sample was removed from the steel mould. This panel is shown in Figure 2(a).

[0140] Method 4 - Making composite panels from waste glass and discarded coffee cups

[0138] A panel of dimensions 240mm x 240mm x 15mm was prepared as follows.

[0141]

[0139] 780 g of mixed waste glass was mixed with 260 g of resin for approximately 5 minutes. 260 g of discarded coffee cups (as aggregates of 10 mm to 40 mm) were then added, followed by mixing for an additional 5 minutes. The resulting mixture was hand laid up into a 240 mm x 240 mm carbon steel mould lined with non-stick Teflon sheet. The surface of the mixture was then smoothed and sealed with a square steel lid. The sealed mould was placed in a hydraulic hot press preheated to 80°C and compressed at a pressure of 500 bar for 60 minutes. The mould was then cooled at room temperature for at least 30 minutes before the sample was removed from the steel mould. This panel is shown in Figure 2(c).

[0142] Example 2

[0140] Composites were prepared by hot pressing as described in Table 1 below.

[0143] [Table 1]

[0144] Material preparation Waste glass

[0141] Several different types of waste glasses were used. The chemical compositions of these glasses were analyzed by X-ray fluorescence analysis (XRF) and are shown in Table 2 below. Most of the glasses contained SiO2, Na2O, and CaO, with small proportions of Al2O3 and MgO.

[0145] [Table 2]

[0146]

[0142] The waste glass X aggregate (particle size less than 5 mm) was dried in a 400°C oven for about 1 hour to about 24 hours (depending on the weight of the glass) to remove moisture and organic matter and to inactivate organic compounds such as paper and plastic in the composite. This minimizes the possibility of cracking the composite during hot pressing manufacturing. A portion of the waste glass aggregate was then crushed into a fine powder using a ring mill. The final particle size of the powder thus obtained was about 75 μm to about 150 μm.

[0147]

[0143] The waste glass can also be modified with silane. The silane selected was 3-glycidoxypropyltrimethoxysilane (CAS no.: 2530-83-8). In this case, the silane can be used at about 1% to about 5% by weight based on the amount of glass intended to be included in the composite. In this example, the silane can be used at 2% by weight based on the amount of glass intended to be included in the composite.

[0148] Paper cups and textile products

[0144] Paper cups and textile products were mechanically shredded and detangled in a granulator to form a fine fibrous filler.

[0149] Coffee grounds

[0145] The as-received coffee grounds were dried in an oven at 100°C for 24 hours before use.

[0150] resin

[0146] The resin used in this example is a polyester resin sold by Allnex under the trade name Polyplex® Fillable Casting resin, which is a pre-promoted, low reactivity orthophthalic polyester resin.

[0151] Additional Ingredients The following ingredients were added: inhibitor (butylated hydroxytoluene), catalyst (t-butyl peroxybenzoate), and mold release agent (calcium stearate). Optionally, a pigment can also be added.

[0152] method

[0148] The conjugates in Table 1 were prepared according to the method illustrated in the following scheme.

[0153] [Table 3]

[0154]

[0149] By crushing the waste glass particles with a particle size of less than 5 mm in a crusher, glass powder with a particle size in the range of about 75-150 μm is obtained. This powder can be used directly for the preparation of the composite. Alternatively, the glass powder can be combined with a coupling agent (about 2% by weight based on the glass powder), water, and ethanol and mixed to form a slurry. The resulting slurry is then dried in an oven at about 100° C. for about 24 hours, and then further crushed to obtain the modified glass.

[0155]

[0150] The ingredients are then added to a sigma blade mixer as follows: Add the corresponding amounts of resin, inhibitor, glass powder, and optional pigments and mix for about 30 minutes; Add catalyst and mix for about 30 minutes; Add the fiber product and mix for approximately 30 minutes.

[0156]

[0151] The catalyst, resin, and inhibitor must be thoroughly mixed before adding to the fiber product. If desired, the resulting mixture can be stored for up to 30 days before hot pressing.

[0157]

[0152] Before making the composite, the press and mould are preheated to about 135-140°C. The calcium stearate is then applied to a preheated carbon steel mould of 300x300 or 500x500 mm. The wet mixture is then hand laid up into the heated mould and the surface is smoothed. A steel square lid is then placed on top and the closed mould is then placed in a hydraulic hot press and compressed at 150 bar pressure for 15 minutes. The mould is then cooled at room temperature for at least 1.5 hours before being demolded. The produced panels are then stored under low load for 24 hours to ensure flatness and to minimise any possible warping.

[0158] Properties of the complex

[0153] The mechanical properties of the composites prepared in Table 1 were evaluated.

[0159] Bending strength

[0154] Flexural strength is defined as the ability of a material to resist deformation under load. It can be measured by a four-point bending test. The maximum bending stress or modulus of rupture (MOR) was measured using an Instron 5982 instrument. The dimensions and support distance of the specimens were determined according to the corresponding thickness. All specimens were cut to 300 x 100 x 12 mm and the outer and inner support distances of the bending test fixture were set at 120 and 60 m, respectively, according to ASTM C880 / 800M. The specimens were subjected to a constant load rate of 4 MPa / min. The results are shown in Figure 3.

[0160]

[0155] Figure 3 shows the bending strength of Samples 1, 2, and 3 by four-point bending test. The bending strength of Sample 1 (i.e., composite panel made from glass with particle size of about 5 mm) was observed to be 10.7 MPa. Sample 2 (i.e., composite panel made from glass powder with size ranging from about 75 μm to about 150 μm) was observed to have almost doubled in strength to 21.2 MPa.

[0161]

[0156] In the case of Sample 3 (i.e., composite panel made from glass powder with size of about 75 μm to about 150 μm and silane), a further improvement of around 3.4 MPa (i.e., about 15%) was observed. This is directly attributable to the presence of silane. The reason for the observed lower strength of Samples 1 and 2 compared to Sample 3 is believed to be due to poor adhesion / lack of wetting between the non-polar glass and the polar resin. The poor adhesion / lack of wetting appears to be overcome by improving the interfacial adhesion between the glass and the polymer by using silane as a coupling agent.

[0162] Compressive strength

[0157] The compressive strength test evaluates the limit of the strength of a specimen under a constant compressive load, and is evaluated by dividing the maximum load by the cross-sectional area of ​​the specimen. The test standard used in this example was in accordance with ASTM C170 / C170-16, using an Instron 5892 instrument with a constant loading rate of 0.5 MPa / s until failure. All specimens had dimensions of 12 x 12 x 12 mm. 3 The dimensions of the cube were set to 10 mm, with a maximum difference of 10% allowed between the axial directions.

[0163]

[0158] Figure 4 shows the compressive strength of samples 1, 2, and 3. On average, sample 1 had a lower compressive strength of 31.31 MPa. Under load, the broad, smooth interface area between the glass aggregate and the resin becomes a defect from which cracks propagate. In the case of samples 2 and 3, this effect is minimized because the finely divided glass powder is densely intertwined and helps to retard the propagation of cracks when the panel is compressed under load. With fine glass powder (75-150 μm), the strength increases from 31.31 to 56.65 MPa (sample 2). In the case of sample 3, a more significant increase in compressive strength is seen. In this regard, the compressive strength is almost doubled to 105.03 due to the higher wetting and bonding between the resin and the glass.

[0164] density

[0159] The density of the test specimens was measured using a precision weighing balance and a volume gas pycnometer. The gas pycnometer instrument accurately determines the volume of a sample using gas displacement techniques and the volume / pressure relationship. The mass and volume measurements are used to calculate the density of the sample.

[0165]

[0160] As shown in Figure 5, the density of sample 1 was found to be 2.01 MPa. This value was 1.94 and 1.96 g / cm for samples 2 and 3, respectively. 3 Sample 1 is made of high density 1-5 mm glass aggregate (2.4-2.5 g / cm 3 ), which increases the overall density of the panel.

[0166]

[0161] The density of each panel is the same as that of natural stone products (>2.5g / cm 3 ) and its combination of low density and high bending strength is expected to make it easier to manufacture thinner countertops / table tops in longer lengths.

[0167] Water absorption test

[0162] The water absorption behavior is useful for judging the durability of composite products in high humidity environments. Excessive water absorption can lead to swelling and strength loss. The samples were first weighed, then immersed in water for 24 hours, taken out, lightly wiped dry, and then weighed again. By measuring the weight difference between the dry sample and the wet sample, the water absorption rate can be calculated according to the following formula:

number

[0168] The results are shown in Table 3 below.

[0169] [Table 4]

[0170]

[0163] From Table 3, it can be seen that the use of glass powder results in the lowest water absorption (i.e., Samples 1 and 2). In this regard, a reduction from about 2% to about 0.65% was observed. A further reduction in water absorption to 0.3% was observed with the addition of a coupling agent. Without wishing to be bound by any particular theory, it is believed that the reduction in water absorption is due to the greater dispersion of the polyester-glass powder matrix (hydrophobic) as well as fewer voids and fine pore areas compared to glass aggregate panels. All of the tested composite panels are comparable to or exceed those of marble slabs, which generally have a water absorption rate of around 2-4%.

[0171] Scratch test

[0164] The scratch resistance of the composite products was also investigated. Scratch tests were carried out using a Macro scratch tester. A sharp diamond tipped indenter was used to scratch the surface of the composite with a constant load of 20N to produce a 5mm gouge mark. The penetration depth profile was then recorded. Due to the heterogeneous nature of the composites, five scratches were produced per sample to ensure accurate results. The results are shown in Figure 6 and Table 4.

[0172] [Table 5]

[0173]

[0165] As can be seen from Table 4, the penetration depth profile of sample 1 is between 14.75 and 187.21 μm. The use of glass powder improves the scratch resistance.

[0174] Abrasion Test

[0166] Abrasion tests were performed to evaluate the performance of the composite products over time. The samples were indented using a 5 mm diameter ruby ​​ball loaded with 10 N and slid back and forth 6000 times at 5 cm / s from the 0 to the 50 mm mark. The depth profile was then measured with a surface profilometer. The results are shown in Figure 6.

[0175] As can be seen from Figure 7, the penetration depth of the composite panels is, on average, small, 10-30 μm, when the abrasion tests are performed on surfaces with a high glass ratio, whereas the abrasion resistance values ​​decrease, reaching as low as 200 μm for glass aggregate panels and 55-70 μm for fine glass panels, when the abrasion tests are performed on surfaces with a high fiber ratio.

[0176]

[0168] Without wishing to be bound by any particular theory, it is believed that the superior abrasion resistance of fine glass panels compared to glass aggregate panels is due to the glass powder and resin combining to form a semi-brittle matrix.

[0177] Contamination Test

[0169] The composite panels were tested for stain resistance against 11 different foodstuffs: milk, coffee, soy sauce, Coca-Cola, beetroot, olive oil, red wine, tomato sauce, turmeric, butter, and lemon. Resistance against three cleaning agents (Windex®, liquid dish detergent, and baking powder) was also tested. The stains were removed after 1, 4, and 24 hours of application by the methods shown in Table 5 below. The cleanability was then classified into six different classes as follows:

[0178] [Table 6]

[0179] The results are shown in Tables 6, 7, and 8.

[0180]

[0170] Figure 8 is a visual representation of stain resistance. Sample 1 was the least stain resistant due to its porosity. Red wine, liquid dish soap, olive oil, and butter stains could not be removed even with the sealer. With the sealer, the stain was observed to be slightly lighter and the stain was allowed to soak for less time. The stain resistance is improved when the panels are made from glass powder. No significant staining is observed on either the unsilane treated or silane treated panels. A slight coffee stain remains on the untreated glass powder / fiber panel.

[0181] [Table 7]

[0182] [Table 8]

[0183] [Table 9]

[0184] Example 3

[0171] Composites were prepared by casting as described in Table 1 below.

[0185] [Table 10]

[0186] Material preparation

[0172] Glass, paper cups, textiles, coffee grounds, and resin were prepared as described above in Example 2. MEKP was used as the catalyst and 4-t-butylcatechol (TBC) was used as the inhibitor. Glass beads were obtained from Burwell Technologies, Revesby NSW.

[0187] method

[0173] The conjugates in Table 9 were prepared according to the method illustrated in Scheme 2 below.

[0188] [Table 11]

[0189]

[0174] By crushing the waste glass particles with a particle size of less than 5 mm in a crusher, glass powder with a particle size in the range of about 75 to 150 μm is obtained. This powder can be used directly for the preparation of the composite. Alternatively, the glass powder can be combined with a coupling agent (about 2% by weight based on the glass powder), water, and ethanol and mixed to form a slurry. The resulting slurry is then dried in a dryer at about 100° C. for about 24 hours, and then further crushed to obtain the modified glass.

[0190] Mold preparation

[0175] The mould base is made from stone slab. The mould sides and top are made from melamine faced particle board. The mould dimensions are 0.09 m 2 ~4m 2In this study, the area was 1200 × 900 × 26 mm. 3 A formwork of the size of 100 mm was made. Preferably, it is necessary to apply a release agent to the form at least 5 times to prevent the mixture from sticking to the stone.

[0191] Casting

[0176] In this example, MixT.1.0 in Table 9 was selected.

[0192]

[0177] First, the inhibitor and resin are mixed and left to stand for at least 2 hours. This allows the resin and inhibitor to react before the catalyst is introduced. Preferably, the inhibitor to resin ratio is 0.1% by weight or less. This is to avoid the situation where the resin mixture is not fully cured. The "inhibitor-resin" mixture is then combined with the glass and catalyst, followed by the filler. The resulting mixture is mixed with a handheld mixer for about 5 minutes. The mixture is then poured into the lower mold and the surface is smoothed with a trowel and scraper. The upper mold is then placed on top of the mixture. A stopper is also used to prevent excessive pressure and ensure uniform thickness throughout the panel. The entire casting mold is then covered with a vacuum bag and the breather is spread evenly over the entire upper mold. The breather is to facilitate the sucking of air from the bag into the vacuum pump. A vacuum pressure of 30 mmHg is applied to the mold for at least 12 to 24 hours. Preferably, the injection, surface smoothing, pressurization, and vacuum pressure application should be performed within about 50-90 minutes, more preferably within about 60 minutes. The casting process is shown in FIG.

[0193]

[0178] The cured composite panel is then removed from the mold the next day. Initial investigations have shown that composite panels containing textiles are more stable compared to panels containing only waste glass / resin. Minimal shrinkage and zero warpage was observed even with shorter vacuum pull times (<24 hours). This may be due to the shrinkage / warpage-preventing properties of the textile fibers and the smaller volume of resin present. Comparative polyester-glass panels without textiles exhibited warpage of around 0.6 mm per meter of board.

[0194]

[0179] Some of the cast panels produced had many micro-pits and a few areas with slightly rough surfaces, which can be easily addressed by manually filling with glass powder / polyester blend / pigment (75 / 25 ratio) and manually sanding with an orbital sander (240 grit).

[0195]

[0180] The panels can then be topcoated with polyurethane (Shore D:80) and left for 24 hours for the coating to fully cure. The hardness of the coating will continue to progress over time.

[0196] Properties of the complex

[0181] The mechanical properties of the composites prepared in Table 9 were evaluated.

[0197] Bending strength

[0182] The flexural strength of the panels was measured according to ASTM C880 / 800M as outlined above. All specimens were cut to 250 x 100 x 26 mm, and the outer and inner support distances of the flexural test fixture were set at 260 and 130 mm, respectively, as required by ASTM. The results are shown in Figure 10.

[0198]

[0183] It can be seen that the flexural strength increases with increasing amount of resin. Between 30% and 35% resin content the difference in flexural strength is less significant (about 1.2 MPa) compared to when 25% resin is present (about 5 MPa).

[0199]

[0184] The bending strength is improved when glass beads are replaced with waste glass powder, as can be seen from Mix T.2.0. The waste glass powder with irregular shape has higher intertwining between particles, which improves bending stress. In contrast, the glass beads with round shape cannot effectively withstand bending stress.

[0200]

[0185] Flexural strength can also be improved by using a coupling agent. In order to obtain high flexural strength, it is necessary to increase the adhesion between the resin and the glass powder filler. Glass powder is an inorganic material and has poor covalent bonding with organic polymer resins. This bonding can be improved by using a coupling agent. In Mix T.2.1, an average improvement of about 1 MPa was observed by adding a coupling agent.

[0201] Compressive strength

[0186] Compressive strength was evaluated as described above. All specimens had dimensions of 26 x 26 x 26 mm. 3 The dimensions of the cube were set to 10 mm, and a maximum difference of 10% was allowed between the axial directions. The results are shown in Figure 11.

[0202]

[0187] A similar trend is observed in the flexural and compressive strength of the corresponding mixes. Higher resin content improves the compressive strength as observed for Mix T.1.0, Mix T.1.1, and Mix T.1.2. The compressive strength also increases by more than 20% to 95 MPa when glass beads are replaced with waste glass powder. An additional increase of 8 MPa is observed between Mix T.2.0 and T.2.1, from 95 to 103 MPa, when a silane coupling agent is added. Mix T.2.2 has 5% less resin than T.2.1, but the performance is only slightly reduced.

[0203] density The density of the samples was measured as described above. The results are shown in Figure 12. From Figure 12, it can be seen that, on average, the density of the panels increased by 1.70 g / cm due to the addition of textile.3 It is expected that the combination of low density and high bending strength will make it easier to manufacture thinner counter tops / table tops in longer lengths.

[0204] Water absorption test

[0189] Water absorption tests were carried out as described above, and the results are shown in Figure 13.

[0205]

[0190] Most of the composite panels containing fibrous fillers were observed to have a water absorption rate of less than 1%. The data presented above is for a 20 x 20 x 20 mm panel without a coating. 3 It should be noted that the measurements were taken on samples of 100% water. The composite performs better than marble slabs, which have a water absorption rate of 2-4%. However, if used in wet environments, it is recommended to apply a clear polyurethane coating to ensure good water resistance and a smooth surface finish.

[0206] Scratch test

[0191] Scratch tests were performed as described above. In this example, scratch tests were performed on rigid polyurethane with Shore D of 80, which would normally be applied on composite panels, or on glass epoxy coatings. As can be seen from Figure 14, from five different scratches, it was observed that the corresponding coatings showed a penetration depth of a minimum of 101.95 to 164.37 μm at a load of 20 N. The coatings are slightly inferior to marble, which showed values ​​of around 80 to 100 μm under the same load. To minimize scratches, the surface of the composite is preferably polished to a satin finish. A self-adhesive protective PET coating layer can also be added to maintain the appearance of the composite and prevent scratches during normal use.

[0207] Abrasion Test

[0192] Abrasion tests were carried out as described above. As can be seen from Figure 15, the coating has a lower penetration depth of 3 μm compared to the generic epoxy coating, which shows a value of 22 μm. The abrasion of the Shore D80 coating is also very good compared to granite and artificial marble, which have penetration depths of -11.6 and 19 μm, respectively.

[0208] Contamination Test

[0193] The stain resistance of the coatings was measured according to the process described above, and the results are shown in Table 10 below and in Figure 16.

[0209] [Table 12]

[0210] Properties of glass / polyester resin and coffee cup / coffee grounds composites.

[0194] The mechanical properties of additional composites made are given below. These composites contain different combinations of glass, resin, fiber, coupling agent, coffee grounds, and coffee cup.

[0211] Bending strength

[0195] The flexural strength of the panels was measured according to ASTM C880 / 800M as outlined above, and the results are shown in Figure 17.

[0212]

[0196] All panels have a polyester:glass:filler ratio of 65:30:5, with some containing a coupling agent at 2% (by weight relative to the amount of glass). Replacing the textile with coffee cups and coffee grounds reduced strength, with flexural strength dropping from 20.5 to 16.27 and 15.53 MPa, respectively. Addition of a silane coupling agent increases flexural strength by 1-20%, as shown in bar graphs 1-2, 3-4, and 5-6 in Figure 17.

[0213]

[0197] The "Bottle Sonic", "fine glass" and "Super fine glass" aggregates are as shown in Table 2 above. "WGP" refers to waste glass X powder (75-150 μm). It is noted that fine waste glass manually ground using a ring mill (bar 1) and bottle sonic (bar 7) have comparable bending strength results, 20.5 and 20.13 MPa, respectively. This is due to the similar fine particle size of the glass powder. It was observed that bending strength decreases with increasing glass particle size. In this regard, the bending strengths of panels made from super fine and fine glass with particle sizes of 0.15-0.71 mm and 0.5-1.0 mm, respectively, are 15.80 and 12.37 MPa.

[0214] Compressive strength

[0198] Compressive strength was evaluated as described above. The results are shown in Figure 18. Similar trends are observed in the flexural and compressive strength of the corresponding composites. When the textile was replaced with coffee cup and coffee grounds, the compressive strength decreased by 27% and 8% to 73.38 and 91.83 MPa, respectively. A slight increase in the average compressive strength of the textile, coffee cup, and coffee grounds panels was observed with the addition of coupling agent, with a significant increase of 18% for the coffee grounds panel.

[0215]

[0199] It is also observed that the compressive strength of bottle sonic (bar 7 for particle size 75-150 μm) is 116.8 MPa, which is significantly higher than that of manually crushed glass of the same particle size. Furthermore, it is observed that the compressive strength decreases with increasing glass particle size. In this regard, the compressive strengths of panels made from super fine and fine glass with particle sizes of 0.15-0.71 mm and 0.5-1.0 mm, respectively, are 74.22 and 59.35 MPa.

[0216] density The density of the samples was measured as described above. The results are shown in Figure 19. From Figure 19, it can be seen that, on average, the density of the fiber-added glass / polyester resin panels was 1.70 g / cm 3 The combination of low density and high bending strength is expected to make it easier to manufacture thinner countertops / tabletops in longer lengths.

[0217] Water absorption test

[0201] Water absorption tests were carried out as described above. The results are shown in Figure 20. From Figure 20, it can be seen that most of the composite panels made from waste glass powder (particle size 75-150 μm) have water absorption less than 1% even after 48 hours of immersion. For panels made from super fine and fine glass aggregates with particle sizes of 0.15-0.71 mm and 0.5-1.0 mm, the water absorption is around 2-2.5% after 24 hours and poor at 2.32-2.5 after 48 hours. This is due to the higher porosity and lower compressibility of the panels. The composites perform better or comparable to marble slabs with water absorption of 2-4%. However, when used in wet environments, it is recommended to apply a clear polyurethane coating to ensure good water resistance and smooth surface finish.

[0218] Silicosis

[0202] In recent years, there has been growing concern about the health effects of silica dust exposure. Silica is found in many construction products, and exposure to it can cause serious medical conditions, including cancer and silicosis. Silicosis is a lung disease caused by inhaling fine crystalline silica dust from cutting, drilling, and grinding granite and quartz-based natural or artificial stones. Crystalline silica particles have been found to promote the development of pulmonary fibrosis, which in the long term increases the risk of lung cancer. Crystalline silica has also been classified as a human carcinogen by the International Agency for Research on Cancer (IARC) (World Health Organization, 1997).

[0219]

[0203] In the present composite, fine silica powder is used as the main component to impart strength and hardness. The silica powder is derived from glass. Glass is composed of non-crystalline / amorphous silica, which is not classified as carcinogenic to humans by the World Health Organisation and does not cause lung damage. In addition to the glass powder, X-ray diffraction analysis was performed on the powder and cutting residue obtained by crushing the composite panel. As shown in Figure 21, no crystalline peaks were observed. This result proves that the composite panel of the present invention is a safe alternative product compared to natural stone and artificial marble, which are mainly composed of quartz.

[0220]

[0204] Based on the above results, the following advantages were recognized for composites containing fiber products: · Fibrous textile fillers help prevent warping of the composite. The introduction of textiles helps to reduce the exotherm temperature during curing. It was observed that the temperature increased from 18 to 21°C. In comparison, the glass / polyester resin panel without auxiliary filler increases by about 20°C, from 18 to 40°C, with 0.1% inhibitor and 1% catalyst.

Claims

1. A composite material comprising waste glass, a binder, and at least one filler selected from a fiber product and coffee grounds, A composite product, wherein the glass is present in an amount of 50% to 90% by weight and the binder is a polymer.

2. The composite product of claim 1 , wherein the binder is present in an amount of from 5% to 45% by weight.

3. The composite product of claim 2, wherein the binder is present in an amount of from 15% to 40% by weight.

4. The composite product of any one of claims 1 to 3, wherein said at least one filler is present in an amount of from 1% to 30% by weight.

5. 5. The composite product of claim 4, wherein said at least one filler is present in an amount of from 2.5% to 15% by weight.

6. 6. The composite product of any one of claims 1 to 5, wherein the glass particle size is between 1 μm and 5 mm.

7. The composite product of any one of claims 1 to 6, wherein the glass is in powder form.

8. The composite product of any one of claims 1 to 7, wherein the polymer is a thermosetting polymer.

9. 9. The composite product of claim 8, wherein the thermosetting polymer is or is derived from an epoxy resin, a polyester resin, or a vinyl ester resin.

10. The composite product according to any one of claims 1 to 9, wherein the textile product is clothing, linen, bedding, a blanket, or a curtain.

11. The composite product according to any one of claims 1 to 10, wherein the textile product is a synthetic textile product.

12. The composite product of any one of claims 1 to 9, wherein said at least one filler is coffee grounds.

13. The composite product of any one of claims 1 to 9, wherein said at least one filler is a fibrous product.

14. A composite product according to any one of claims 1 to 13, comprising between 60% and 100% waste material.

15. The composite product of any one of claims 1 to 14, further comprising a coating.

16. A composite product according to any one of claims 1 to 15 in the form of a panel or a tile.

17. 1. A method for making a composite article, comprising: The method comprises: (i) forming a mixture comprising waste glass, a binder, and at least one filler selected from textile products and coffee grounds; (ii) forming the composite product by applying heat and pressure to the mixture; The method of claim 1, wherein the glass is present in the mixture in an amount of from 50% to 90% by weight and the binder is a polymer.

18. The method of claim 17, wherein the binder is present in the mixture in an amount of from 5% to 45% by weight.

19. The method of claim 18, wherein the binder is present in the mixture in an amount of from 15% to 40% by weight.

20. The method according to any one of claims 17 to 19, wherein the at least one filler is present in the mixture in an amount of from 1% to 30% by weight.

21. The method of claim 20, wherein the at least one filler is present in the mixture in an amount of from 2.5% to 15% by weight.

22. The method according to any one of claims 17 to 21, wherein the glass is pre-treated with a coupling agent.

23. The method of claim 22, wherein the coupling agent is a silane.

24. The method according to any one of claims 17 to 23, wherein the glass is in powder form.

25. The method according to any one of claims 17 to 24, wherein the polymer is a thermosetting resin.

26. 26. The method of claim 25, wherein the thermosetting resin is an epoxy resin, a polyester resin, or a vinyl ester resin.

27. Step (i) is carried out as follows: - combining and mixing said glass and said binder, and then adding said at least one filler so as to obtain said mixture: The method according to any one of claims 17 to 26.

28. Step (i) is carried out as follows: - forming a first mixture comprising said glass and said binder and mixing said first mixture; - forming a second mixture by combining a catalyst with the first mixture and mixing the second mixture; and - combining said at least one filler with said second mixture and mixing to obtain said mixture; The method according to any one of claims 17 to 26.

29. A method according to any one of claims 17 to 28, wherein step (ii) is carried out by filling the mixture into a mould and pressing in a hydraulic press.

30. 1. A method for making a composite article, comprising: The method comprises: (i) forming a mixture comprising waste glass, a binder, and at least one filler selected from textile products and coffee grounds; (ii) filling the mixture into a mould; (iii) drawing a vacuum on the mixture; Including, The method of claim 1, wherein the glass is present in the mixture in an amount of from 50% to 90% by weight and the binder is a polymer.

31. The method of claim 30, wherein the binder is present in the mixture in an amount of from 5% to 45% by weight.

32. The method of claim 31, wherein the binder is present in the mixture in an amount of from 15% to 40% by weight.

33. The method according to any one of claims 30 to 32, wherein the at least one filler is present in the mixture in an amount of from 1% to 30% by weight.

34. 34. The method of claim 33, wherein the at least one filler is present in the mixture in an amount of from 2.5% to 15% by weight.

35. The method according to any one of claims 30 to 34, wherein the glass is pre-treated with a coupling agent.

36. 36. The method of claim 35, wherein the coupling agent is a silane.

37. The method according to any one of claims 30 to 36, wherein the glass is in powder form.

38. The method of any one of claims 30 to 37, wherein the polymer is a thermoset.

39. 39. The method of claim 38, wherein the thermosetting resin is an epoxy resin, a polyester resin, or a vinyl ester resin.

40. Step (i) is carried out as follows: - forming a first mixture comprising an inhibitor and said binder and mixing said first mixture; - forming a second mixture by combining the glass and catalyst with the first mixture and mixing the second mixture; and - combining at least one filler with said second mixture and mixing to obtain said mixture; 40. The method according to any one of claims 30 to 39.

Citation Information

Patent Citations

  • Fiber reinforced thermoplastic resin composite material

    JP1993154840A

  • Fiber reinforced thermoplastic resin composite material

    JP1994039834A

  • Method for recycling waste

    JP1994071647A

  • Water-base polyurethane resin dispersion and coating agent

    JP1997235460A

  • Fiberboard and its manufacturing method

    JP2001334508A